Magnetohydrodynamics simulation of magnetic reconnection process based on the laser-driven Helmholtz capacitor-coil targets - Xing, Chunqing; Ping, Yongli; Zhao, Xu; An, Weiming; Zhong, Jiayong (Frontiers in Physics, 2024)
This study is based on the magnetohydrodynamics simulation method and utilizes the FLASH code to investigate the laser-driven magnetic reconnection physical process of the Helmholtz capacitorcoil target. The simulation model incorporates the laser driving effect, and the external magnetic field consistent with the Helmholtz capacitor-coil target is written in. This approach achieves a magnetic reconnection process that is more consistent with the experiment. By changing the resistivity, subtle differences in energy conversion during the evolution of magnetic reconnection are observed. Under conditions of low resistivity, there is a more pronounced increase in the thermal energy of ions compared to other energy components. In simulations with high resistivity, the increase in electrons thermal energy is more prominent. The simulation gives the evolution trajectory of magnetic reconnection, which is in good agreement with the experimental results. This has important reference value for experimental research on the low-β magnetic reconnection.